Influence of structural changes on electrical and magnetic properties of the Co84Fe5,3Si8,5B2,2 amorphous alloy - Đukić S.R.; Simeunović Radojko L.; Maričić Aleksa M. (Science of Sintering, 2005)
The crystallization process of the Co84Fe5.3Si8.5B2.2 amorphous alloy examined by differential scanning calorimetry (DSC) exhibits three exothermal steps at Tcr1=649K, Tcr2=800K, and Tcr3=838K. The rate constants of the first relaxation process (determined at 598K and 623K) are k1=5*10-4 s and k2=8*10-4 s and the corresponding activation energy Ea1=26.23 kJ/mol. The data for the relaxation process before the second crystallization step (determined at 683K and 713K) are k3=14.5*10-4 s and k4=17.5*10-4 s and the corresponding activation energy Ea2=60.0 kJ/mol. The process of structural relaxation in non-isothermal and isothermal conditions was studied by analysis of the results of measurements of the thermo electromotive force (TEMF). From the change of the temperature coefficient of TEMF that follows each annealing process, the relative electronic state density changes at the Fermi level were determined: ΔN21/N2=5,45%, ΔN22/N2=5,76%, ΔN23/N2=7,57% and ΔN24/N2=9,85%.